2007
DOI: 10.1197/j.aem.2007.04.010
|View full text |Cite
|
Sign up to set email alerts
|

Free Fluid in Morison's Pouch on Bedside Ultrasound Predicts Need for Operative Intervention in Suspected Ectopic Pregnancy

Abstract: Free intraperitoneal fluid found in Morison's pouch in patients with suspected ectopic pregnancy may be rapidly identified at the bedside by EP-performed US and predicts the need for operative intervention.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(17 citation statements)
references
References 8 publications
(7 reference statements)
0
16
0
Order By: Relevance
“…A high index of suspicion for ruptured ectopic pregnancy is required, and ultrasound findings can help to increase clinical suspicion of ruptured ectopic pregnancy (free peritoneal fluid, empty intrauterine cavity, adnexal mass) as well as haemodynamic instability because of the resultant haemoperitoneum. Presence of free fluid in Morison's pouch may predict the need for operative management [6]. Ruptured ectopic pregnancy combines two limitations of care found in the maritime medicine environment -absent surgical capabilities, and lack of blood products.…”
Section: Discussionmentioning
confidence: 99%
“…A high index of suspicion for ruptured ectopic pregnancy is required, and ultrasound findings can help to increase clinical suspicion of ruptured ectopic pregnancy (free peritoneal fluid, empty intrauterine cavity, adnexal mass) as well as haemodynamic instability because of the resultant haemoperitoneum. Presence of free fluid in Morison's pouch may predict the need for operative management [6]. Ruptured ectopic pregnancy combines two limitations of care found in the maritime medicine environment -absent surgical capabilities, and lack of blood products.…”
Section: Discussionmentioning
confidence: 99%
“…PPOCUS may play a more useful role in determining patients needing prompt operative care – in those with ruptured ectopic pregnancy. Rather than focusing on identifying an IUP, visualisation of fluid in the hepatorenal space (Morison’s pouch) by PPOCUS has been found to be strongly predictive of the need for operative intervention with a positive likelihood ratio of 112 [11]. In an appropriately trained EP, PPOCUS takes less than 5 min to complete [11].…”
Section: Discussionmentioning
confidence: 99%
“…Rather than focusing on identifying an IUP, visualisation of fluid in the hepatorenal space (Morison’s pouch) by PPOCUS has been found to be strongly predictive of the need for operative intervention with a positive likelihood ratio of 112 [11]. In an appropriately trained EP, PPOCUS takes less than 5 min to complete [11]. A recent meta-analysis found that there are significant time savings with PPOCUS, especially at night where access to formal departmental US is limited [12].…”
Section: Discussionmentioning
confidence: 99%
“…There was strong evidence to support its use with significant heterogeneity within the pooled data [6]. A prospective observational study looked at the presence of fluid in the hepatorenal space (Morrison's pouch) -its identification signalling the likelihood of requiring operative management; nine out of 10 identified patients using PoCUS went on to require operative management after formally correlated investigations [7]. Chest physicians utilise PoCUS in performing thoracocentesis.…”
Section: Review Pocus In Practicementioning
confidence: 99%